Materiais a base de colágeno com capacidade de autorreparo - Camila Silva Brey Gil (2013)
Polyurethane microcapsules containing diisocyanate in their interior were synthetized by varying the stirring speed (1500, 1000 and 700 rpm) and the type of isocyanate (4,4-diphenylmethane diisocyanate (MDI) and isophorone diisocyanate (IPDI)), to yield a total of 6 different types of microcapsules. Their characterization via Scanning Electron Microscopy (SEM) and Optical Microscopy showed that the highest stirring speeds used during the preparation produced microcapsules with smaller diameter. According to the thermogravimetric analysis (TG), the stirring speed did not affect the thermal properties of the produced material. It was also possible to verify the weight loss of the encapsulated reagents, as well as the degradation temperature of the microcapsules wall. Through FTIR, the presence of N=C=O groups specific from isocyanates in the microcapsules interior was confirmed. Thus, it was found that the microcapsules had great potential for applications involved in self-repairing techniques. Collagen films doped with the microcapsules were produced in order to evaluate the system self-repairing capacity. As control group, a pure collagen film was used, while other films were prepared with 5% and 10% microcapsule concentrations of all six types produced. The characterization through SEM of the cryogenic fractures of the films indicated the presence and a high level of dispersion of the microcapsules in the matrix. The structural integrity and the thermal behavior of the collagen matrix in the films were proved respectively via FTIR and TG. For both techniques, no influence of the microcapsules over the pure collagen properties was observed. The tensile test indicated that the incorporation of microcapsules to the collagen matrix caused the value of the elasticity modulus to increase, which revealed an increase in the rigidity of the material. All of the samples containing microcapsules showed a decrease in the deformation in respect to pure collagen. No results indicated an increase in the tensile strength of the samples containing microcapsules when compared with the pure matrix. In order to evaluate the self-repairing capacity of the developed devices, samples were submitted to a 20 mm strain (to develop micro-cracks in the material). They were then left to stand for 20 minutes (to allow any cross-link reaction to develop), and a new tensile test was performed that was named, in this dissertation. paused tensile test. With the results obtained in this test, it was possible to observe that the pure collagen film suffered no alteration concerning its mechanical properties. The films doped with the microcapsules, which presented mechanical properties typical of a cross-linked network, were the ones with 5% (w/w) concentration, with microcapsules produced at stirring speeds of 1000 and 700rpm, and all of the ones with 10% concentration. Based on these results, the potential for self-repairing of the developed devices was proved.